Consider the intellectual property aspects of technology transfers in the higher ed world. Issue 1 (22nd August 2019) - Reed, Julie L.; Wagner, Justin D.
Abstract : Many scenarios exist for technology transfer in commercializing intellectual property in the university environment. Sponsoring organizations may pay to fund research and then use any rights they have in their own company, or use them to found a subsidiary. Government‐funded research may be transferred to a government lab or agency. The university itself may decide to "spin out" technology developed by a faculty member within the university. This generally means the university will assist in the founding of a startup company to commercialize the research. This last scenario is of particular interest here, and the discussion that follows focuses on the intellectual property considerations in such a transfer, rather than the structure of the company itself.